1999
DOI: 10.1161/01.cir.99.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Activation of β 2 -Adrenergic Receptors Hastens Relaxation and Mediates Phosphorylation of Phospholamban, Troponin I, and C-Protein in Ventricular Myocardium From Patients With Terminal Heart Failure

Abstract: Background-Catecholamines hasten cardiac relaxation through ␤-adrenergic receptors, presumably by phosphorylation of several proteins, but it is unknown which receptor subtypes are involved in human ventricle. We assessed the role of ␤ 1 -and ␤ 2 -adrenergic receptors in phosphorylating proteins implicated in ventricular relaxation. Methods and Results-Right ventricular trabeculae, obtained from freshly explanted hearts of patients with dilated cardiomyopathy (nϭ5) or ischemic cardiomyopathy (nϭ5), were paced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
99
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 44 publications
5
99
2
Order By: Relevance
“…In cardiomyocytes, the extrusion and sequestration of free calcium during diastole is dependent on cyclic AMP, is modulated by b-receptors, and is influenced by several ion transport mechanisms including the Na + /H + exchanger. [30][31][32][33][34][35][36] Cardiac b-receptors couple to a G-protein-stimulated adenylcyclase, which in turn stimulates cyclic AMP-dependent regulatory mechanisms. 30,31,33,37 Recent studies in rodent cardiomyocytes revealed that b 2 -receptors couple to G-proteins, which lead to inhibition of cyclic AMP formation downstream.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiomyocytes, the extrusion and sequestration of free calcium during diastole is dependent on cyclic AMP, is modulated by b-receptors, and is influenced by several ion transport mechanisms including the Na + /H + exchanger. [30][31][32][33][34][35][36] Cardiac b-receptors couple to a G-protein-stimulated adenylcyclase, which in turn stimulates cyclic AMP-dependent regulatory mechanisms. 30,31,33,37 Recent studies in rodent cardiomyocytes revealed that b 2 -receptors couple to G-proteins, which lead to inhibition of cyclic AMP formation downstream.…”
Section: Discussionmentioning
confidence: 99%
“…Data were acquired using an IonOptix setup and analyzed with IonWizard 5.0 software (IonOptix, Milton, MA). Cross-sectional area (CSA) of the atrium was determined from the length and weight of the muscle after the experiment, assuming a density of 1.063 (26).…”
Section: Methodsmentioning
confidence: 99%
“…␤ 2 -Adrenoceptors participate with ␤ 1 -adrenoceptors in the mediation of cardiostimulant effects of epinephrine in human atrium (Gille et al, 1985;Hall et al, 1990;Kaumann et al, 1999), ventricle (Kaumann and Lemoine 1987;Gille et al, 1985;Bristow et al, 1989;Kaumann et al, 1999;Del Monte et al, 1993;Molenaar et al, 2000), and sinoatrial node (Daul et al, 1995). Norepinephrine can also cause cardiostimulation through human ␤ 2 -adrenoceptors (Kaumann and Lemoine, 1987;Hall et al, 1990).…”
mentioning
confidence: 99%